Utilization of Artificial Intelligence (AI) in Learning Islamic Religious Education at SMP IT Bina Ilmi Palembang - Adriyansyah, Adriyansyah; Yulia, Yulia; Fitriani, Ayu; Oviyanti, Fitri; Maryamah, Maryamah (Journal of Educational Sciences, 2025)
This study was motivated by the development of technology, especially Artificial Intelligence (AI), which began to be integrated into Islamic Religious Education (PAI) learning. Traditionally, PAI learning is often conducted using the lecture method, which has limitations in providing interactivity and personalization. Therefore, this study aims to examine the utilization of AI technology in improving the effectiveness of Islamic Education learning at Bina Ilmi IT Junior High School Palembang. This study used a qualitative approach with descriptive method, where data were collected through observation and in-depth interviews with PAI subject teachers. The results showed that the application of AI in PAI learning was able to have a significant impact on improving students' understanding of the material taught. Teachers utilize AI to provide more interactive materials, data-based learning evaluations, and learning tailored to students' individual needs. Furthermore, the integration of AI not only improves learning effectiveness, but also encourages students to be more active and motivated in understanding Islamic values. This study contributes to understanding how technology can support the transformation of traditional learning methods to be more modern, relevant, and adaptive to the needs of today's digital generation.